The emergence, persistence and current challenges of coffee forest gardens: A case study from Candelaria Loxicha, Oaxaca, Mexico - Aguilar-Støen, M.; Angelsen, A.; Stølen, K.; Moe, S.R. (2011)
In many parts of Latin America coffee is produced in forest garden systems, which fulfill a variety of household needs, enhance food security, and conserve biodiversity. We investigate drivers in the emergence, persistence, and decline of coffee forest gardens, using a case study in southern Mexico and combining historical, socioeconomic, and institutional analysis. Social, cultural, and political benefits linked to forest gardens are important drivers of change. The analysis supports the hypothesis that forest gardens emerge in places where they complement broader land use systems, land tenure is relatively secure, and the local economy is a combination of cash- and subsistence-based activities. The article further illustrates how the international coffee agreement and social-welfare programs supported the emergence of forest gardens. Low coffee prices, changes in land tenure, and reduced availability of labor could result in the eventual abandonment of coffee forest gardens.